Structural, morphology and electrical properties of layered copper selenide thin film - Ying, Josephine Chyi Liew; Talib, Zainal Abidin; Mat Yunus, Wan Mahmood; Zainal, Zulkarnain; Shaari, Abdul Halim; Abd. Moksin, Mohd Maarof; Wan Yusoff, Wan Mohd Daud; Lim, Kean Pah (Versita Warsaw and Springer, 2009)
Thin films of copper selenide (CuSe) were physically deposited layer-by-layer up to 5 layers using thermal evaporation technique onto a glass substrate. Various film properties, including the thickness, structure, morphology, surface roughness, average grain size and electrical conductivity are studied and discussed. These properties are characterized by X-ray diffraction (XRD), atomic force microscopy (AFM), ellipsometer and 4 point probe at room temperature. The dependence of electrical conductivity, surface roughness, and average grain size on number of layers deposited is discussed.